The Microteaching Course Benefits towards the Students of English Education Study Program in Teaching Practice - Wanda Amran; Rizkariani Sulaiman; Awaluddin Syamsu; Muhammad Affan Ramadhana (South Sulawesi Education Development (SSED), 2023)
The aim of this study was to assess the advantages and responses experienced by students during their micro-teaching course, which serves as preparation for their teaching practice (PPL). The study employed a quantitative research method and was conducted within the English Education Program at Universitas Muslim Indonesia. The study's population consisted of eighth-semester students enrolled in the English Education Department, encompassing three classes. Data was collected using a Likert scale questionnaire, with a total of 60 students sampled from the entire population. Data collection was solely through the questionnaire. The results of the data analysis indicated that students held significantly positive perceptions regarding the benefits of micro-teaching courses, with 77% expressing very positive views. Additionally, students' responses to these courses were predominantly positive.